Graduating outcome based education diploma in science students': Insight achievement / Wan Siti Atikah Wan Omar and Sarah Laila Md Jan - Wan Omar, Wan Siti Atikah; Md Jan, Sarah Laila (2013)
Graduating year is the most important year in students' life. Academic excellences with good personal qualities are displayed in their seniority. Students ought to accomplish some parts of the specific knowledge and skills, as addressed in the Malaysia Qualification Framework by the Ministry of Education (formerly known as Ministry of Higher Education). This system is well known as outcome based education (OBE). Every program offered in the university has to line up with the OBE documents, proposing the ideal outcome of their respective graduate. However, the students' actual performance is yet to be measured Hence, this paper will be conferring on the Diploma in Science (AS120) students' perception on their own achievement in completing the programme. An open ended questionnaire were distributed to AS120 graduating students in the second semester of December 2012-April 2013, comprising of44 and 30 students of part five and part six, respectively. The students' insights were found contradictory with the outcome of programme. Moreover, the cognitive achievement measured by sub-sampling the respondents in a biology written test found that the students overestimated their capabilities. Some of the students were found, surprisingly, to have little or no knowledge of OBE system in our earlier approach. Nonetheless, they agreed that some activities in the class and assessment justification by the lecturers covered their cognitive, psychomotor and affective skills. As conclusion, although the OBE was implemented throughout the years, the AS120 graduating students are yet far from acknowledging the details of the OBE system. Students were also suggesting that they improve their learning skills via psychomotor activities such as laboratory works, rather than having lectures.